Technology and intimacy : choice or coercion : 12th IFIP TC 9 International Conference on Human Choice and Computers, HCC12 2016, Salford, UK, September 7-9, 2016, Proceedings /: choice or coercion : 12th IFIP TC 9 International Conference on Human Choice and Computers, HCC12 2016, Salford, UK, September 7-9, 2016, Proceedings. (2016) - Unknown
No abstract available